Tinjauan Etis-Pedagogis Terhadap Peran Guru Dalam Mendidik Anak Sekolah Minggu Di GKJ Salatiga Utara - Kristania, Cindy Uzia; Ludji, Irene; Buke, Nimali Fidelis (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2024)
Abstract: This research aims to describe and analyze the role of teachers in educating Sunday school children at GKJ North Salatiga from an ethical-pedagogical perspective. This research uses a qualitative approach. Qualitative data was collected through semi-structured interviews and participant observation. The theory used in the analysis is based on ethical studies from Reinhold Niebuhr and pedagogical studies from Thomas Groome. The research results show that education for children is essential, and the church needs to participate in it. The efforts made by GKJ North Salatiga in educating Sunday school children include instilling Christian values or giving the example of Jesus. Jesus' example is also an example of ethical behavior offered by Niebuhr. The ethical values contained in the research are respecting others, giving appreciation, love, forgiveness, helping, sharing, caring, fairness, justice, and humility. In pedagogical studies, it was found that teachers not only taught the example of Jesus through theory, but it was also reflected in the lives of Sunday school teachers. Teachers also use various creative teaching methods and media in the learning process. Creative teaching supports children to understand God's word better. Teachers at GKJ North Salatiga also manage the Sunday school well and in a structured manner. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis peran guru dalam mendidik anak sekolah Minggu di GKJ Salatiga Utara ditinjau dari perspektif etis-pedagogis. Penelitian ini menggunakan pendekatan kualitatif. Data-data kualitatif dikumpulkan melalui wawancara semi-terstruktur dan observasi partisipatif. Teori yang digunakan dalam analisis adalah kajian etis dari Reinhold Niebuhr dan pedagogis dari Thomas Groome. Hasil penelitian menunjukkan bahwa pendidikan untuk anak-anak adalah hal yang penting, dan gereja perlu untuk ambil bagian di dalamnya. Upaya yang dilakukan GKJ Salatiga Utara dalam mendidik anak-anak sekolah Minggu, adalah dengan menanamkan nilai-nilai kristiani atau keteladanan Yesus. Keteladanan Yesus juga merupakan contoh perilaku etis yang ditawarkan oleh Niebuhr. Adapun nilai-nilai etis yang ditemukan dalam penelitian, yaitu, menghargai sesama, memberikan apresiasi, kasih, pengampunan, menolong, berbagi, peduli, adil, kesetaraan dan rendah hati. Dalam kajian pedagogis, ditemukan bahwa guru tidak hanya mengajarkan keteladanan Yesus melalui teori, tetapi juga dicerminkan dalam kehidupan guru sekolah Minggu. Dalam proses pembelajaran, guru juga menggunakan berbagai metode dan media mengajar yang kreatif. Pengajar yang kreatif mendukung anak-anak untuk lebih memahami firman Tuhan. Guru di GKJ Salatiga Utara juga mengelola sekolah Minggu dengan baik dan terstruktur.